Comparative cytomorphological studies on a diploid, a triploid and a tetraploid clone of Hevea brasiliensis (Willd. ex. Adr.de Juss.) Muell. Arg. - Saraswathyamma C K; Licy J; Nazeer M A; Panikkar A O N; Premakumari D (Indian Journal of Natural Rubber Research, 1988)
Cytomorphological observations were made on an induced tetraploid clone, an evolved triploid clone and a diploid clone of Hevea brasiliensis (Willd. ex. Adr. de Juss.) Muell. Arge. Both the tetraploid and the triploid had varied number of leaflets, large floral parts and stomata and thicker leaflets compared to those of the diploid. In growth and morphological features at the early stage of growth, the triploid appeared to be intermediate between the diploid and tetraploid. Meiotic studies of the tetraploid showed large number of bivalents, while frequency of univalents, trivalents and quadrivalents was comparatively low. The triploid exhibited univalents, bivalents and trivalents. Anaphase I showed unequal segregation and formation of laggards and micronuclei in the tetraploid and the triploid, the frequency of their occurrence being more in the triploid. Pollen stainability was very low in the triploid.
Keywords: Amphidiploid; Diploid; Hevea brasiliensis; Meiosis; Tetraploid; Triploid